Production Cost Structure, Sales Growth, Inflation, and Profitability in Food and Beverage Companies - Livia Sandi; Rulyanti Susi Wardhani; Sumiyati Sumiyati (LPPM STIE Krakatau, 2026)
Purpose: This study aims to analyze the effect of production cost structure and sales growth on profitability and examine the role of inflation as a moderating variable in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Methodology: This study employed a quantitative approach using secondary data from 19 companies selected through purposive sampling, resulting in 57 observations. The data were analyzed using Moderated Regression Analysis (MRA) with the assistance of SPSS. Results: The results show that the production cost structure has a significant negative effect on profitability, with a regression coefficient of -0.312 (p= 0.001). Meanwhile, sales growth has no significant effect on profitability, with a coefficient of 0.027 (p= 0.765). Furthermore, inflation does not moderate the effects of production cost structure or sales growth on profitability. Conclusions: The findings indicate that company profitability is more strongly influenced by internal factors, particularly production cost efficiency, than by external factors such as inflation. The relationship between the main variables is direct and not influenced by inflationary conditions. Limitations: This study is limited to a three-year observation period and uses a limited number of variables; therefore, it does not fully capture all factors that may influence profitability. Contribution: This study contributes to the profitability literature and offers practical guidance for management and investors to assess performance through cost efficiency and sales growth.